The effects of the wobble board on archery accuracy at 30 meters for archers - Resi, Septian; Mulaksito Mulyadi, Rekyan Woro; Nugroho, Agung Wahyu; Sunaryo; Nugroho, Wisnu; Kurniawan, Arif; Fitoni Nuradila, Muh. Batistuta; Widyastuti, Candra (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2025)
This research aims to determine whether wobble board training methods affect shooting accuracy in archers at a distance of 30 meters. This research uses a quasi-experimental method with a One Group Pretest-Posttest Design. The research sample consisted of 12 archers aged 15–18 years, selected from the SELABORA Archery of FIK UNY. The instrument used was archery at a 30 meters distance. The data analysis technique employed Normality Test using SPSS 25 software, followed by a Homogeneity Test to determine whether sample variances derived from the same population were equal. Based on the research findings and discussion: Based on the analysis of the archery accuracy data of SELABORA Archery FIK UNY, the calculated t value (5,437) > t table (2,20), and the p value (0,000) < of 0.05. Therefore, it can be concluded that wobble board training significantly affects archery accuracy at 30 meters among SELABORA Archery FIK UNY.